AB0992 Knee lavage versus intra articular hyaluronan in advanced knee osteoarthritis. (23rd January 2014) - Mortada, M.; Elewa, E.A.
Abstract : Background: Many patients with advanced knee osteoarthritis (OA) who are indicted for total knee joint replacement (TKR) are unfit for operation or refuse it for different reasons. Palliative treatment for this group of patients may be important for decreasing pain and improving function. Objectives: The aim of this study was to compare the benefits of the knee joint lavage (KJL) and intra-articular hyalurinic acid injections (HAIs) in patients with advanced OA of the knee. Methods: We performed a single-centre, single blind, randomized, parallel group trial comparing KJL and HAIs. Patients with advanced knee OA (Kellgren/Lawrence score 4) who are indicted for TKR and unfit or refuse to have TKR, were randomized to either knee lavage using the 2 needle technique (1) or a weekly intra-articular injection of hyalurinic acid for 3 weeks. Patients were followed for 12 months. The primary outcome measures were the Western Ontario and McMaster Universities OA Index total pain score WOMAC (a Likert scale). Results: seventy patients were recruited of whom 36 received KJL and 34 received HAIs. At the end of the 1st month, there was a reduction in the WOMAC pain score of 80% and 40% in KJL and HAIs groups respectively. At this time point just (32 patients) 88.9% and (17 patients) 50% of patients in KJL and HAIs groups respectively felt that their knee pain had improved compared to baseline. At the end of the 6th month post injection, there was a reduction in the WOMAC pain score of 50% and 10% in KJL and HAIs groups respectively. At this time point just (21patients)58.3% and (4 patients)11.8% of patients in KJL and HAIs groups respectively felt that their knee pain had improved compared to baseline. At the end of the 9th month post injection, there was a reduction in the WOMAC pain score of 25% and 5% in KJL and HAIs groups respectively. At this time point just 27.7%(10 patients) and 5.9% (2 patients) of patients in KJL and HAIs groups respectively felt that their knee pain had improved compared to baseline. By the end of the 12th month, none of patients in both groups felt that his knee pain had improved compared to baseline and there was no reduction in WOMAC pain score At the ends of 1st, 6th and 9th months, the improvement in WOMAC pain score and the number of subjects reporting an improvement in symptoms was significantly greater in the KJL group compared to the HAIs group (p<0.001). Conclusions: In patients with advance OA, KJL improved pain better than HAIs and for a longer duration. References: Ayral X. Best Pract Res Clin Rheumatol. 2005 Jun;19(3):401-15. Disclosure of Interest: None Declared